(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2025)
This paper presents the design of a mixed channel to establish a direct connection between fresh food producers and various consumer markets in the department of Cochabamba, Bolivia. The general objective of this initiative is to design a mixed channel for the reception and delivery of fresh food, considering the demand from households and the HORECA sector (Hotels, Restaurants, Cafés) in the city. To achieve this, data collection was conducted through interviews and surveys, taking into account producers, intermediaries, and consumers (households and the HORECA sector). In the channel design, the distribution points were located in the central and northern zones, along with a storage and distribution center. For the distribution model design, mixed options were considered. The Buy Online and Pick Up in Store (BOPS) algorithm will model the connection between producers and convenience points in the city. Additionally, a heuristic algorithm for the Vehicle Routing Problem (VRP) will be employed to define optimal delivery routes to the HORECA channel and pickup points for households. This will establish a direct distribution channel for fruits and vegetables, considering not only the processes within the collection center but also determining the most efficient delivery routes based on consumer needs.